Global wellposedness of cubic Camassa–Holm equations. (March 2016) - Zhang, Qingtian
Abstract: In this paper, we study the Cauchy problem of cubic Camassa–Holm equation. This equation is derived from a model of shallow water dynamics. We prove the global existence of entropy weak solution to this problem in space H 1 with its derivative in B V . The stability and uniqueness of entropy weak solution are obtained in W 1, 1 .